The Rise of Right-Wing Extremism in European Union - Stevkovski, Ljupcho (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
It is a fact that in the European Union there is a strengthening of right-wing extremism, radical right movement, populism and nationalism. The consequences of the economic crisis, such as a decline in living standards, losing of jobs, rising unemployment especially among young people, undoubtedly goes in favor of strengthening the right-wing extremism. In the research, forms of manifestation will be covered of this dangerous phenomenon and response of the institutions. Western Balkan countries, as a result of right-wing extremism, are especially sensitive region on possible consequences that might occur, since there are several unresolved political problems, which can very easily turn into a new cycle of conflicts, if European integration processes get delayed indefinitely.